COMPARATIVE ANALYSIS OF SERVICE QUALITY IN TRAVELAGENT APPLICATIONS USING E-SERVQUAL AND IPA - Febrianti, Amalia Rizki; Utomo, Rio Guntur; Yasirandi, Rahmat (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
This research compares the service quality of travel agent applications, which are KAI Access and Traveloka, in booking train tickets using the E-Service Quality and Importance Performance Analysis (IPA) methods. This service quality is measured based on seven dimensions of E-Service Quality, including efficiency, fulfillment, reliability, privacy, responsiveness, compensation, and contact. Data were collected through questionnaires from 340 respondents who use the KAI Access and Traveloka applications to book train tickets. The collected data were then analyzed descriptively using the Importance Performance Analysis (IPA) technique to identify priority attributes for improvement based on user satisfaction and importance levels. Based on the Gap Analysis and evaluation of 340 respondents, both the KAI Access and Traveloka apps require improvements as they still need to meet user expectations. The service quality of KAI Access and Traveloka shows significant differences across various dimensions measured by the E-Servqual and Importance Performance Analysis (IPA) methods. The research results are expected to provide recommendations for both applications to improve service quality and user satisfaction. The comparison of service quality is also expected to provide insights into the strengths and weaknesses of each application in providing train ticket booking services.